Komposisi Zooplankton Di Perairan Rawa Banjiran Sungai Rungan Kota Palangkaraya - Infa Minggawati (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2014)
This fieldwork aims to determine the composition, abundance and diversity of zooplankton in the river flood swamps Rungan Palangkaraya city, this study was conducted in October and December 2013. Research method used was purposive sampling method, with sampling at four observation stations. The results showed that there are two phyla obtained by the phylum Rotifera and Capepoda, with the highest abundance found in October 1567ind/l that the first station  and in December there were at stations III and IV is 69 ind/l. Zooplakton diversity was highest in October at station III, while for December are on station III and IV. Average range of water quality in October and December: temperature 26.7 to 28.7 ° C, depth 2.4 to 6.4 m, DO from 3.2 to 3.4 ppm and pH 3.6 to 39.